The Relationship between the Role of Quality Control Circles and Improved Nurses’ Compliance with Standard Operating Procedures at Mitra Medika Tanjung Mulia Hospital - Suherni Suherni; Lilis Pujiati; Chairul Munir; Heni Triana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Hospitals are required to maintain service quality and patient safety through consistent adherence to Standard Operating Procedures (SOPs). Quality Control Circles (Gugus Kendali Mutu; GKM) serve as an internal quality control mechanism that supports quality planning, audit implementation, monitoring, coaching, and follow-up of audit findings. This study aimed to examine the association between the role of Quality Control Circles and nurses’ compliance with SOPs at Mitra Medika Tanjung Mulia Hospital. A quantitative descriptive-analytic study with a cross-sectional design was conducted from November 2025 to March 2026, involving 35 active members of the Quality Control Circles selected through total sampling. Data were collected using structured questionnaires and analyzed through univariate analysis, bivariate analysis using Pearson Chi-square and Fisher’s Exact Test, and multivariate analysis using binary logistic regression. The results showed that 65.7% of respondents perceived the role of Quality Control Circles as good, while 74.3% of nurses were categorized as compliant with SOPs. Bivariate analysis revealed a significant association between the role of Quality Control Circles and nurses’ SOP compliance (χ² = 10.171; p = 0.001; Fisher’s Exact Test = 0.003). Multivariate logistic regression showed that nurses who perceived the role of Quality Control Circles as good had higher odds of complying with SOPs, although the association was not statistically significant after controlling for age, gender, educational background, and years of service (AOR = 6.228; 95% CI = 0.247–157.196; p = 0.267). These findings indicate that Quality Control Circles are relevant to strengthening SOP compliance, but their role should be reinforced through continuous supervision, structured feedback, and integrated quality improvement strategies. Keyword: Quality Control Circles; nurses’ compliance; Standard Operating Procedures; hospital quality management; patient safety